2022
DOI: 10.1002/esp.5396
|View full text |Cite
|
Sign up to set email alerts
|

Morpho‐sedimentary evolution of a microtidal meandering channel driven by 130 years of natural and anthropogenic modifications of the Venice Lagoon (Italy)

Abstract: Tidal channels form the pathways for tidal currents to propagate and distribute clastic sediments and nutrients, thus providing a primary control on tidal-landscape ecomorphodynamics. Most tidal channels in both estuarine and lagoonal environments have a tendency to meander, yet very few studies exist that investigate the full spectrum of processes controlling tidal meander morpho-sedimentary evolution.The Venice Lagoon (Italy) offers a unique opportunity to shed light on this topic, because a long record of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 104 publications
3
7
0
Order By: Relevance
“…This result is in agreement with findings from earlier studies, which found average tidal meander sinuosity to be restricted within a narrow range of values (1.3 < χ <2.2; see Marani et al, 2002). The tidal meander are consistent with changing local tidal flow asymmetry (see Finotello et al, 2019Finotello et al, , 2022. Thus, channel sinuosity may be reduced as a consequence of periodic shifts in local asymmetries of tidal flows.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in agreement with findings from earlier studies, which found average tidal meander sinuosity to be restricted within a narrow range of values (1.3 < χ <2.2; see Marani et al, 2002). The tidal meander are consistent with changing local tidal flow asymmetry (see Finotello et al, 2019Finotello et al, , 2022. Thus, channel sinuosity may be reduced as a consequence of periodic shifts in local asymmetries of tidal flows.…”
Section: Discussionsupporting
confidence: 91%
“…The reduced sinuosity displayed by tidal meanders might be partially attributed to the frequent changes in local tidal asymmetries that can change the planform evolution trajectory of tidal meanders. As observed in previous studies, changes in the migration direction of tidal meander are consistent with changing local tidal flow asymmetry (see Finotello et al, 2019, 2022). Thus, channel sinuosity may be reduced as a consequence of periodic shifts in local asymmetries of tidal flows.…”
Section: Discussionsupporting
confidence: 89%
“…Since the construction of the jetties, changes in the tidal regime within the lagoon have been much more sustained than the typical periodic, multi-annual variations induced by the nodal modulation of tides in the Adriatic Sea, which are in the order of 4% of the characteristic tidal range (Amos et al, 2010;Valle-Levinson et al, 2021). Between 1909 and1973, the tidal range within the lagoon increased as much as 25% on average (L. D 'Alpaos, 2010;Ferrarin et al, 2015;Tomasin, 1974), with local changes that can be even more pronounced (Finotello et al, 2019;Finotello, Capperucci, et al, 2022;Silvestri et al, 2018). Changes in the lagoon hydrodynamics due to the construction of the jetties, coupled with eustatic sea-level rise (average value 1.23±0.13 mm/year between 1872 and 2019; 2.76±1.75 mm/year between 1993 and 2019; see Zanchettin et al 2021), had important impacts on the lagoon morphological evolution, triggering positive morphodynamic feedbacks.…”
Section: Geomorphological Settingmentioning
confidence: 99%
“…Although secondary currents akin to those found in river meanders have been observed and modeled in meandering salt‐marsh creeks and large estuarine tidal channels (Finotello, Canestrelli, et al., 2019; Finotello, Ghinassi, et al., 2020; Finotello et al., 2022; Kranenburg et al., 2019; Nidzieko et al., 2009; Pein et al., 2018; Somsook et al., 2020, 2022), their presence in sinuous mudflat channels has yet to be demonstrated. In fact, previous studies (e.g., Choi, 2011; Choi & Jo, 2015; Ghinassi et al., 2019; Kranenburg et al., 2019) suggested that the morphodynamic processes governing meander evolution in intertidal mudflat settings can differ greatly from the classic secondary‐current‐driven lateral channel migration mechanism acting in vegetated fluvial and intertidal plains.…”
Section: Introductionmentioning
confidence: 99%